1985
DOI: 10.1113/jphysiol.1985.sp015723
|View full text |Cite
|
Sign up to set email alerts
|

Post‐natal development of pyramidal tract neurones in kittens.

Abstract: SUMMARY1. The post-natal development of pyramidal tract neurones (p.t.n.s) was investigated in twenty-one barbiturate-anaesthetized kittens from birth to 28 days of age using a combination of electrophysiological and anatomical techniques.2. P.t.n. responses were recorded intracellularly as well as extracellularly with glass micropipettes filled with horseradish peroxidase (HRP) on stimulation of the medullary pyramid and cerebellar nuclei.3. Latency histograms of antidromic responses of p.t.n.s were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
(67 reference statements)
3
9
0
Order By: Relevance
“…Immature axons, however, have low conduction velocities and thus long conduction times (Song et al, 1995b;Olivier et al, 1997), making it difficult to judge whether observed synaptic potentials are monosynaptic. The issue is f urther complicated by the fact that there are considerable variations in conduction velocity, even among axons in a single group of neurons during development (Oka et al, 1985;Song et al, 1995b). Nevertheless, the results presented here together support the view that the rising phase of the cortically evoked potentials was composed of monosynaptic EPSPs.…”
Section: Epsp Amplitude As An Index For Studying the Development Of Fsupporting
confidence: 68%
See 1 more Smart Citation
“…Immature axons, however, have low conduction velocities and thus long conduction times (Song et al, 1995b;Olivier et al, 1997), making it difficult to judge whether observed synaptic potentials are monosynaptic. The issue is f urther complicated by the fact that there are considerable variations in conduction velocity, even among axons in a single group of neurons during development (Oka et al, 1985;Song et al, 1995b). Nevertheless, the results presented here together support the view that the rising phase of the cortically evoked potentials was composed of monosynaptic EPSPs.…”
Section: Epsp Amplitude As An Index For Studying the Development Of Fsupporting
confidence: 68%
“…The latencies of all EPSPs are plotted as a function of age in Figure 3D. These latencies are comparable to the conduction times of kitten cortical axons from the cortex to the trapezoid body, at corresponding ages (Oka et al, 1985). Because the trapezoid body is further away from the cortex than is the RN, these results support the view that the EPSPs are monosynaptic.…”
Section: The Epsps Evoked By Cortical Stimulation Appear To Be Monosysupporting
confidence: 63%
“…The CV values estimated in our study (0.85-1.21 m/s) were 1/10th that of adult (Alstermark et al 2004;Bannister and Porter 1967;McComas and Wilson 1968;Mediratta and Nicoll 1983;Porter and Lemon 1993;Stewart et al 1990). In fact, neonatal CVs of the CS tract of postnatal monkeys and cats are 10 times slower than those of adult animals (Oka et al 1985;Olivier et al 1997). The CV values we estimated in early postnatal rat are consistent with the decreased CV in other species.…”
Section: Discussionmentioning
confidence: 99%
“…After week 8, skill is noticeably greater; this is that age that we can begin to train kittens to reach (unpublished observations; Martin et al 2000). Clearly this improvement is not due to CS myelination, which is well developed by week 4 (Oka et al 1985). Presynaptic corticospinal site development has not yet been examined in the primate.…”
Section: Role Of Myelination In Maturation Of Cs Functionmentioning
confidence: 99%